Marketing Strategy: Promotion of Kacang Asin Pak Tani Brand Products at Tanjung Anom Village - Husnah, Muslimatul; Suhairi, Suhairi; Dharma, Budi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research focuses on developing a marketing strategy for the “Kacang Asin Pak Tani” product. This product is a home industry engaged in selling dry food and snacks. Sales of Pak Tani’s Salted Peanuts have continued to increase from 2019 to 2022, but interview results show that this product has not implemented a good marketing strategy, including offline and online promotions, market segmentation, and other marketing mixes. In developing an effective marketing strategy, the 4P concept (Product, Price, Place, Promotion) is an important basis. The method used in this research is the descriptive qualitative method, with the observation approach and interview as a data collection technique, research data consists of secondary and primary data. Primary data was generated from interviews with home industry owners of Salted Peanut Products, employees, and consumers. Secondary data includes graphic data of the sales cycle for four years, EFAS and IFAS data, as well as SWOT analysis obtained from Kacang Asin Pak Tani company. The researchers also use literature reviews as a theoretical foundation that can support solving the problem being studied. Research results, based on the SWOT analysis can be seen that the strategy used is in quadrant 1, this position is a very profitable position, by implementing a strategy that supports aggressive growth policies (Grow Oriented Strategy). So, this is a strategy that can be carried out by the Kacang Asin Pak Tani Brand Product so that the strengths, weaknesses, opportunities, and threats of the business can be identified. As a suggestion, in terms of promotion, the “Kacang Asin Pak Tani” brand needs to develop a more effective promotion strategy to increase consumer awareness of the products and brands offered.